2021
DOI: 10.1021/acs.est.1c00515
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Induced Hepatotoxicity under Cypermethrin: Involvement of the Crosstalk between Nrf2/Keap1 and NF-κB/iκB-α Pathways Regulated by Proteasome

Abstract: Cypermethrin (CMN) is a man-made insecticide, and its abuse has led to potential adverse effects, particularly in sensitive populations such as aquatic organisms. The present study was focused on the toxic phenotype and detoxification mechanism in grass carp (Ctenopharyngodon idella) after treatment with waterborne CMN (0.651 μg/L) for 6 weeks in vivo or 6.392 μM for 24 h in vitro. In vivo, we describe the toxic phenotype of the liver of grass carp in terms of pathological changes, serum transaminase levels, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“… 25 In addition, studies have shown that Nrf2 is decoupled from Keap1 when the body is affected by ROS, interacts with antioxidant response element (ARE), regulates the activity of ARE-dependent antioxidant genes (such as SOD and GSH-Px), and maintains the homeostasis of redox. 26 Our experimental results clearly confirmed that CD could reduce the level of oxidative stress in mice with LPS-induced ALI. Furthermore, LPS-induced inflammation is regulated by a variety of immune cells.…”
Section: Discussionsupporting
confidence: 78%
“… 25 In addition, studies have shown that Nrf2 is decoupled from Keap1 when the body is affected by ROS, interacts with antioxidant response element (ARE), regulates the activity of ARE-dependent antioxidant genes (such as SOD and GSH-Px), and maintains the homeostasis of redox. 26 Our experimental results clearly confirmed that CD could reduce the level of oxidative stress in mice with LPS-induced ALI. Furthermore, LPS-induced inflammation is regulated by a variety of immune cells.…”
Section: Discussionsupporting
confidence: 78%
“…40 Our study also found that HgCl 2 inhibited TH1 cytokines and induced TH2 cytokines in the thymus and BF. Oxidative stress is always accompanied by environmental toxins, [41][42][43] especially heavy metal exposure, [44][45][46] and is an important inducer of the release of pro-inflammatory cytokines. 36 The pro-oxidative stress of Hg has been well documented by mechanisms involving attack on mitochondria, 47 binding of sulfhydryl groups, 48 promotion of ROS production, 6 and weakening of anti-oxidation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is an important transcription factor regulating cellular redox homeostasis. Under physiologic conditions, Nrf2 concentration is low, whereas under oxidative stress, it is activated and translocated from the cytoplasm into the nucleus [ 22 ]; this can trigger downstream target genes responsible for detoxification and elimination of harmful substances [ 23 ]. The protein expression level of Kelch-like ECH-associated protein 1 (keap1) is a negative regulator of Nrf2 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%